AssemblX: a user-friendly toolkit for rapid and reliable multi-gene assemblies. Issue 10 (27th January 2017) - Hochrein, Lena; Machens, Fabian; Gremmels, Juergen; Schulz, Karina; Messerschmidt, Katrin; Mueller-Roeber, Bernd
Abstract: The assembly of large DNA constructs coding for entire pathways poses a major challenge in the field of synthetic biology. Here, we present AssemblX, a novel, user-friendly and highly efficient multi-gene assembly strategy. The software-assisted AssemblX process allows even unexperienced users to rapidly design, build and test DNA constructs with currently up to 25 functional units, from 75 or more subunits. At the gene level, AssemblX uses scar-free, overlap-based and sequence-independent methods, allowing the unrestricted design of transcriptional units without laborious parts domestication. The assembly into multi-gene modules is enabled via a standardized, highly efficient, polymerase chain reaction-free and virtually sequence-independent scheme, which relies on rare cutting restriction enzymes and optimized adapter sequences. Selection and marker switching strategies render the whole process reliable, rapid and very effective. The assembly product can be easily transferred to any desired expression host, making AssemblX useful for researchers from various fields.